Film and Ritual: epistemological dialogs between filmic anthropology and anthropological practice - Reyna,Carlos P. (2012)
This article discusses the dialog between filmic anthropology's procedures and methods and anthropological practice, with a focus on ritual, which is captured by the moving image in a more direct and fluid way. For this, the ritual of reproduction and preservation of cattle in Santiago, a peasant village in the Peruvian Andes is used as an empirical base. As an anthropologist-filmmaker I will try to make explicit the relationship between the observed process filmed and the informant, combining two important epistemological grids: Claudine de France's deferred observation, and Clifford Geertz's interpretation from the native's point of view. Finally, based on this experience, I will make some observations about the use of methodological approximations from filmic anthropology in anthropological practice, between film and anthropology.